The Relationship Between Motivation and Adherence of Chronic Kidney Disease in Undergoing Hemodialysis Therapy in The Hospital - Agu, Kimi Duimeer; Tambunan, Evelyn Hemme (NUTRIX, 2024)
The prevalence of chronic kidney disease (CKD) continues to increase and hemodialysis therapy is one of the main renal replacement therapies in CKD patients. There is a relationship between motivation and adherence to hemodialysis therapy in several previous studies. However, this study has never been conducted at the research location so this study aims to investigate the relationship between motivation and adherence of patients with CKD in undergoing hemodialysis therapy. The research design used in the study was descriptive quantitative correlation with a cross-sectional approach to explore the relationship between motivation and adherence of CKD patients in undergoing hemodialysis therapy. The population in this study were CKD patients who were undergoing hemodialysis therapy at Advent Hospital Bandung, totaling 100 patients. With the Simple Random Sampling technique and using the Michael and Isaac table, 79 respondents participated in the study. The instruments used in this study were the ESRD-AQ questionnaire (The End-Stage Renal Disease Adherence Questionnaire) and a valid motivation questionnaire to measure the motivation and adherence of patients with CKD in undergoing hemodialysis therapy. Univariate descriptive analysis and Spearman's rank bivariate correlation were used to answer the identified research questions. The results showed that most of the GHG patients had high motivation in undergoing hemodialysis therapy. It is suggested that healthcare should improve the quality of medical services for patients with GGK who undergo hemodialysis therapy. Further research is needed to investigate the factors associated with motivation and adherence using qualitative design. Kepatuhan dan motivasi merupakan hal penting untuk menetukan keberhasilan pengobatan terapi hemodialisa. Penelitian ini bertujuan untuk menginvestigasi hubungan antara motivasi dan kepatuhan pasien GGK dalam menjalani terapi hemodialisa. Desain penelitian yang digunakan dalam penelitian adalah deskriptif kuantitatif korelasional dengan pendekatan cross-sectional untuk mengeksplorasi hubungan antara motivasi dan kepatuhan pasien GGK dalam menjalani terapi hemodialisa. Populasi dalam penelitian ini adalah pasien GGK yang sedang menjalankan terapi hemodialisa di Rumah Sakit Advent Bandung yang berjumlah 100 pasien. Dengan teknik pengambilan sampel Simple Random Sampling dan menggunakan tabel Michael dan Isaac, 79 responden berpartisipasi dalam penelitian. Instrumen yang digunakan dalam penelitian ini adalah kuesioner ESRD-AQ (The End-Stage Renal Disease Adherence Questionnaire) dan kuesioner motivasi yang telah valid untuk mengukur motivasi dan kepatuhan pasien GGK dalam menjalani terapi hemodialisa. Analisis deskriptif univariat dan korelasi bivariat Spearman’ rank digunakan untuk menjawab identifikasi masalah penelitian. Hasil penelitian menunjukkan bahwa sebagian besar pasien GGK memiliki motivasi tinggi dalam menjalani terapi hemodialisa yaitu berjumlah 44 responden (55,7%), sebagian besar pasien GGK patuh dalam menjalani terapi hemodialisa dengan jumlah 46 pasien (58,23%) dan terdapat hubungan antara motivasi dengan kepatuhan pasien GGK dalam menjalani terapi hemodialisa dengan nilai p-value adalah 0,001. Disarankan agar pelayanan kesehatan meningkatkan kualitas pelayanan medis bagi pasien GGK yang menjalani terapi hemodialisis. Penelitian lebih lanjut diperlukan untuk menyelidiki faktor-faktor yang berhubungan dengan motivasi dan kepatuhan dengan menggunakan desain kualitatif.